2018
DOI: 10.1128/jcm.00325-18
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Carbapenemase Production Directly from Blood Culture by Colorimetric Methods: Evaluation in a Routine Microbiology Laboratory

Abstract: The aim of this study was to evaluate the two rapid colorimetric methods (CNPt-Direct and Blue-Carba) for the detection of carbapenemase production directly from blood culture in a routine microbiology laboratory. The methods were initially evaluated on spiked blood cultures with 61 carbapenemase-positive isolates. Afterwards, they were used in blood cultures (314 samples were evaluated) obtained from patients in a routine microbiology laboratory during a period of 6 months. The colorimetric methods were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…A range of strategies may be useful in achieving this goal. According to the study results, our hospitals implemented the following recommendations for ICU patients: (i) regular rectal screening [36,37] will be useful to improve this clinical strategy. We found no differences in 30-day mortality rates among patients who received colistin-base, CAZ-AVI-based, or other treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…A range of strategies may be useful in achieving this goal. According to the study results, our hospitals implemented the following recommendations for ICU patients: (i) regular rectal screening [36,37] will be useful to improve this clinical strategy. We found no differences in 30-day mortality rates among patients who received colistin-base, CAZ-AVI-based, or other treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…3 Double-disk synergy test for detection of strains belongs to class A β-lactamases, Modified Hodge test to detect class A β-lactamases and meropenem E-test strip to identify class B β-lactamases is common tests. 13,14 One of the most critical advantages of phenotypic methods is their cost-effectiveness. Of course, the fatality of these methods and the low speed of diagnosis should be mentioned from its main disadvantages, and the need to use sensitive and rapid molecular methods along with these phenotypic methods is essential.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting finding was the decreased diagnostic sensitivity for the detection of VIM activity in anaerobic versus aerobic bottles (53.6% and 100%, respectively), raising the hypothesis that this enzyme may be downregulated, inactivated, or rapidly degraded in anaerobic bottles. Previous studies have shown high sensitivity values when metallo-␤-lactamases are detected directly from BCs by colorimetric methods (8)(9)(10)(11), immunochromatographic tests (14,16), or MALDI-TOF-based hydrolysis assays (17,18), even though these screening were performed only on spiked aerobic BC bottles. More recently, Cointe et al have reported the low reproducibility of the RESIST-4 O.K.N.V.…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of genotypic diagnostic methods for the detection of ␤-lactamase-encoding genes in blood cultures (BCs) are currently available, they are expensive procedures requiring skilled personnel and are not able to identify all ESBL-or carbapenemase-encoding genes (6). Thus, during the last decade, several phenotype-based assays have been developed to detect ESBL or carbapenemase production in BCs, including colorimetric methods (7)(8)(9)(10)(11)(12)(13), immunochromatogenic assays (14)(15)(16), and ␤-lactam hydrolysis assays combined with matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) (17)(18)(19)(20).…”
mentioning
confidence: 99%